Development of the MyLathe Application Based on Discovery Learning to Improve Student Learning Outcomes in Lathe Machining at Vocational High Schools - Kresnadi, Muh. Elvio Putra; Hadromi, Hadromi; Widjanarko, Dwi (Jurnal Penelitian Pendidikan, 2025)
This study aims to develop a learning application called MyLathe for eleventh-grade students in the Mechanical Engineering program at vocational high schools (SMK). The application is designed to support the discovery learning model and can be accessed via smartphones, laptops, and web platforms, enabling flexible and user-friendly learning experiences. The research employs the ADDIE development model, consisting of five phases: Analysis, Design, Development, Implementation, and Evaluation. The feasibility of MyLathe was evaluated through expert validation. Media expert validation yielded an Aiken’s V value of 0.93, while content validation scored 0.96, both indicating high validity. The reliability coefficients for both media and content exceeded 0.40, meeting acceptable standards. The effectiveness of the application was measured using an independent sample t-test, which yielded a t-value of 11.561, exceeding the critical t-table value of 1.999. This indicates a statistically significant improvement in student learning outcomes. Additionally, the N-Gain analysis showed an increase in the average pre-test score from 46.06 to a post-test score of 62.67 in the experimental class, with a comparable pre-test average of 46.84 in the control class. Practicality testing involving both teachers and students yielded a score of 92%, classified as “highly practical.” These findings suggest that the MyLathe application is a valid, reliable, effective, and practical digital learning tool for enhancing learning in machining subjects at vocational high schools.